FINANCIAL PERFORMANCE OF SMALL AND MEDIUM BUSINESSES IN MAKASSAR: THE ROLE OF INTELLECTUAL CAPITAL AND COMPETITIVE ADVANTAGE - Parmitasari, Rika Dwi Ayu; Abdullah, Wahidah; Alwi, Zulfahmi; Haris, Hariyati (Jurnal Iqtisaduna, 2019)
Small and Medium Enterprises in the city of Makassar continue to experience rapid development. One of the challenges in Small and Medium Enterprises in Makassar is the low financial performance of SMEs. This is caused by low productivity because the quality of human resources is still low because of the lack of knowledge and entrepreneurial competence. Good management of intellectual capital can improve the company's financial performance. This study aims to examine the effect of intellectual capital on financial performance with a competitive advantage as an intervening variable in small and medium enterprises in the city of Makassar. This research conducted a quantitative method with an associative approach. Data of this research was primary data collected through questionnaire surveys. The research used multiple linear regression and path analysis with IBM Statistics SPSS 21. The results showed that intellectual capital had a positive and significant effect on the financial performance of SMEs in Makassar. Furthermore, intellectual capital impacted the competitive advantage of SMEs in Makassar city positively and significantly. Competitive advantage was also proven to have a positive and significant influence on the financial performance of SMEs in Makassar. The results of this study also indicated that competitive advantage was a mediating variable between the relationship of intellectual capital to the financial performance of SMEs in Makassar.